Implementation Of The Preceptorship Model In Midwife Care: Scooping Review - Ana Dyah Aliza; Farida Kartini (International Journal of Health Science and Technology, 2021)
Background: The Preceptorship model has different rules in clinical practice learning for health students at a midwifery clinic. The purpose of this literature review is to find out the perspective of the implementation of preceptorship from various groups of student education levels on midwifery care as a whole. Method: This article takes databases from PubMed, Wiley, Google Scholar, and ScienceDirect published between 2010-2019 with the keywords "preceptorship", "perspective" and "student" in combination. The inclusion criteria in this article are primary research, articles between the years 2000-2019, in English and Indonesian. This article uses the PRISMA flow diagram framework. Results: Preceptorship can help preceptors to improve the effectiveness of their teaching and learning environment so that they can perform clinical skills to improve the quality of education. Appears tools or instruments used to evaluate Preceptorship. However, this evaluation is known to have not been standardized. Conclusion: The application of preceptorship in midwifery clinical practice varies. This is due to the absence of a standard preceptorship instrument.